Attitudes, believes, determinants and organisational barriers behind the low seasonal influenza vaccination uptake in healthcare workers – A cross-sectional survey. Issue 23 (31st May 2018) - Boey, Lise; Bral, Charlotte; Roelants, Mathieu; De Schryver, Antoon; Godderis, Lode; Hoppenbrouwers, Karel; Vandermeulen, Corinne
Highlights: Despite recommendation, flu vaccination in healthcare workers remains low in Europe. Factors of low coverage in HCW in both hospitals and nursing homes were assessed. Few healthcare workers see influenza vaccination as a duty not to harm patients. Misconceptions about influenza vaccination still circulate among healthcare workers. Additional guidance of the organisation of seasonal influenza campaigns is needed. Abstract: Background: Seasonal influenza threatens hospitalised patients and residents of nursing homes annually. Due to age and chronic disease their protection following immunisation is diminished. Additional immunisation of direct contacts and in particular healthcare workers (HCWs) has proven added value. As vaccination coverage in HCWs remains low, we aimed to gain insight in the factors behind the demotivation for influenza vaccination. Methods: Attitudes and believes towards influenza vaccination and socio-demographic and professional determinants were surveyed in 5141 Belgian HCWs from 13 hospitals and 14 nursing homes. Additionally, influenza campaign coordinators of the participating healthcare institutions were interviewed about the factors of success/failure in their campaigns. Results: The mean vaccination coverage registered by the participating healthcare institutions was 40.4% in the hospitals and 45.3% in the nursing homes. Overall, up to 90% of HCWs found it important not to infect their patients. However, only 20% of non-vaccinated HCWs considered influenza vaccination a duty to not harm their patients. Up to 40% of unvaccinated staff believed they could get influenza after vaccination and that vaccination weakens their immune system. Also, only about 20% of unvaccinated staff thought to have a high chance of getting influenza. Reasons for unvaccinated staff to get vaccinated in the future are self-protection and protection of family members. Factors that positively influenced vaccination coverage are encouragement by supervisors (OR, hospitals: 7.1, p < 0.001; nursing homes: 7.5, p < 0.001) and well-organized vaccination campaigns with on-site vaccination. Factors that negatively affected vaccination coverage are misconceptions about influenza and its vaccine (OR, range 0.1–0.7, p < 0.001 for most misconceptions) and underestimation of the risk of contracting influenza by patients or HCWs (OR of perceived susceptibility, range 2.1–5.1, p < 0.001 for most factors). Conclusion: There is a need for guidance for the organization of seasonal influenza campaigns, in which education, communication and easy accessible vaccination are promoted.